2023
DOI: 10.1123/jsr.2021-0383
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Improvements Following Unilateral Home-Based Training in Plantar Flexors: A Potential for Cross-Education in Rehabilitation

Abstract: Context: Cross-education (CE) refers to neuromuscular gains in the untrained limb upon contralateral limb training. To date, only laboratory-based exercise programs have demonstrated CE. Home-based exercise prescription eliciting CE could have greater clinical applicability. Objective: To determine the effect of an 8-week, home-based unilateral strength training intervention on isokinetic muscle strength, muscular excitation, and power in trained and untrained plantar flexors. Design: Randomized controlled tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This review showed mixed exercise in the form of traditional, cluster, or other types of exercises in an intensity range (705% 1 RM-100% 1 RM) could produce cross-education as much as 6.5-45% (13,17,21,31,36,38). This review has also shown that if exercises are applied with a high intensity, such as 90% 1 RM, but in low volume (5 set/1 rep), could not significantly produce cross-education (31).…”
Section: Mixed Exercisementioning
confidence: 99%
See 3 more Smart Citations
“…This review showed mixed exercise in the form of traditional, cluster, or other types of exercises in an intensity range (705% 1 RM-100% 1 RM) could produce cross-education as much as 6.5-45% (13,17,21,31,36,38). This review has also shown that if exercises are applied with a high intensity, such as 90% 1 RM, but in low volume (5 set/1 rep), could not significantly produce cross-education (31).…”
Section: Mixed Exercisementioning
confidence: 99%
“…Cross-education is limited to the homologous and heterologous muscles (5) of the untrained limb because the effect of cross-education requires the neural contributions of the trained muscles responsible for maintaining cross-education (10). While there is much evidence about cross-education, in recent years, most studies have shown that different training protocols created varied cross-education results (1,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). It has shown that the rate of increase in strength of the untrained limb varied from 45.2% (26), 30% (15), and 11% (16) to 5% (12) in the untrained limb.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations